“Is There No One Here Who Speaks to Me?” Performing Ethnic Encounter in Bohemia and Moravia at the Turn of the 17th Century - Scott L. Edwards (Diasporas: Circulations, Migrations, Histoire)
This article investigates the musical performance of ethnic encounter following the transfer of the imperial court of Rudolf II from Vienna to Prague in 1583. As the Bohemian capital more than tripled in size in the following decades, musical culture began to reflect the international make up of the city with ramifications that could be felt across Bohemia and Moravia. Musical forms such as the multilingual quodlibet and the messanza responded to the newfound cultural preeminence of Italian music as well as a rapidly expanding Italian diaspora, while exposing the communicative challenges unique to the region’s multilingual environment.